2008
DOI: 10.1177/039463200802100107
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Lactoferrin Inhibits the Efficiency of Invasion of Respiratory A549 Cells of Different Iron-Regulated Morphological Forms of Pseudomonas Aeruginosa and Burkholderia Cenocepacia

Abstract: Pseudomonas aeruginosa and Burkholderia cenocepacia are two important opportunistic respiratory pathogens of cystic fibrosis (CF) patients. Infections caused by these microorganisms are particularly difficult to eradicate because they are usually highly resistant to several currently available broad-spectrum antibiotics. Lactoferrin (Lf), a glycoprotein found in physiological fluids of mammals and present at high concentrations in infected and inflamed tissues, plays an important role in the natural defence me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…Taken together, these data provide strong evidence for iron chelation to be an effective adjunctive therapy in treating P. aeruginosa lung infections. Treatment with the host iron-binding protein lactoferrin reduces both the epithelial invasion of Burkholderia cenocepacia and the inflammatory response of CF bronchial epithelial cells to Burkholderia cenocepacia biofilm (Berlutti et al, 2008). Whether these effects are the result of iron chelation or an alternative mechanism is unknown.…”
Section: Novel Therapeutic Strategies Targeting Iron Acquisition In Cmentioning
confidence: 99%
“…Taken together, these data provide strong evidence for iron chelation to be an effective adjunctive therapy in treating P. aeruginosa lung infections. Treatment with the host iron-binding protein lactoferrin reduces both the epithelial invasion of Burkholderia cenocepacia and the inflammatory response of CF bronchial epithelial cells to Burkholderia cenocepacia biofilm (Berlutti et al, 2008). Whether these effects are the result of iron chelation or an alternative mechanism is unknown.…”
Section: Novel Therapeutic Strategies Targeting Iron Acquisition In Cmentioning
confidence: 99%
“…In any case, the intracellular lifestyle ensures the bacteria a protective niche to replicate, persist, and avoid the host defenses. Lf interferes with the bacterial invasion process of host cells, probably through its binding to bacterial and/ or cell surfaces [15,[95][96][97]. This ability is not related to the Lf iron-chelating function because apo-saturated, iron unsaturated, and iron-saturated Lf exerts an inhibiting activity against the microbial internalization.…”
Section: Antimicrobials Of the Human Airway: Lactoferrin A Componentmentioning
confidence: 99%
“…Apo-bLf was prepared by the depletion of iron in 0.1 M citric acid, pH 2.3, containing 500 mg/l disodium EDTA, followed by exhaustive dialysis against deionized water. Iron saturated-bLF was obtained by adding adequate molar ratio of ferric ions according procedure described by Berlutti et al (2008). The iron saturation rates were approximately 4.5% for apo-bLf, 19.4% for native bLf, and 95.6% for iron saturated-bLf.…”
Section: Bovine Lactoferrinsmentioning
confidence: 99%
“…Previously, we demonstrated that bovine lactoferrin (bLf) was able to influence the efficiency of invasion of different iron-regulated morphological forms of B. cenocepacia; bLf showed to efficiently inhibit invasion of alveolar epithelial cells by freeliving, aggregates or biofilm bacterial forms ironinduced (Berlutti et al 2008). To further investigate the inhibitory action of bLf against B. cenocepacia, we focused this study on the examination of the interaction between bLf and B. cenocepacia, by testing the ability of bLf to bind to bacterial surface.…”
Section: Introductionmentioning
confidence: 99%